Capitan Pepe - Empaynado, Carlos
Is there a qualification to lead? Jose a.k.a. Pepe (Joseph Estrada) did prove to the people in their barrio that the real concern and love to your constituent is the key to a good public service. Capitan Pepe is a story of dirty and funny side of politics even in the small barrio and it was even made exciting when romance tried to find its place despite the conflict.--https://www.imdb.com/title/tt0411209/plotsummary?ref_=tt_ov_pl